A method of digital processing of the shape of impulses applied to investigation of promising scintillators - Markochev, S.S.; Eremin, N.V.; Arbuzov, V.I. (Functional Materials, 2013)
Spectrometer on the basis of digital storage oscilloscope Tektronix TDS 7704B for the study of scintillation characteristics of promising scintillators is described. Digital waveforms of anodic impulses from PMT photomultiplier were stored and processed in off-line mode. The measured maximum counting rate of impulses was 1.8·10⁵ imp./s. The results of the experimental research of the scintillation characteristics of enriched ⁶Li -silicate glass, manufactured in SIC "S.Vavilov State Optical Institute", is presented. The energy resolution (FWHM) of the peak from ⁶Li (ntherm,α)Treaction of thermal neutrons with ⁶Li was 23 %. Scintillation times of the glass for α- and γ -sources were measured; the possibility of additional discrimination of thermal neutrons and γ -quanta by the shape of impulses is presented.